2001
DOI: 10.1073/pnas.191268198
|View full text |Cite
|
Sign up to set email alerts
|

Alu -mediated inactivation of the human CMP- N -acetylneuraminic acid hydroxylase gene

Abstract: Inactivation of the CMP-N-acetylneuraminic acid hydroxylase gene has provided an example of human-specific genomic mutation that results in a widespread biochemical difference between human and nonhuman primates. We have found that, although a region containing a 92-bp exon and an AluSq element in the hydroxylase gene is intact in all nonhuman primates examined, the same region in the human genome is replaced by an AluY element that was disseminated at least one million years ago. We propose a mechanistic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
115
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 56 publications
1
115
0
1
Order By: Relevance
“…This region is 8100 and 8099 bp long for the gorilla and the chimpanzee, respectively, but it varies from 7611 to 7637 bp in the human. The region contains a human-specific AluY that replaced a genomic region, including functionally important exon 6 (Hayakawa et al 2001). The AluY insertion is found in all human chromosomes examined, but not in the chimpanzee or in the gorilla.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This region is 8100 and 8099 bp long for the gorilla and the chimpanzee, respectively, but it varies from 7611 to 7637 bp in the human. The region contains a human-specific AluY that replaced a genomic region, including functionally important exon 6 (Hayakawa et al 2001). The AluY insertion is found in all human chromosomes examined, but not in the chimpanzee or in the gorilla.…”
Section: Methodsmentioning
confidence: 99%
“…Hayakawa et al (2001) studied the genomic sequences around exon 6 of various primate species and found that whereas the exon and a nearby AluSq element are present in all nonhuman primates, they are completely replaced by a young AluY element in humans. On the basis of the finding of a potential target-priming sequence by the Alu poly(A) tail located in the 59 region immediately adjacent to the upstream deletion boundary, an Alu-mediated replacement of a genomic region was proposed as the underlying molecular mechanism (Hayakawa et al 2001). Subsequently, Chou et al (2002) took multiple approaches to estimate the timing of this Alu-mediated replacement.…”
mentioning
confidence: 99%
“…Inactivation of CMAH evidently involved replacement of an ancient AluSq present in the humanchimpanzee ancestral genome with a younger sahAluY (sialic acid hydroxylase AluY) that is related to the AluYb8 subfamily (18). We used the timing of human Alu integration events to calculate the inactivation time of CMAH.…”
Section: Analysis Of Alu Sequences To Time the Inactivation Of The CMmentioning
confidence: 99%
“…This mutation is homozygous in all human populations but absent in great apes (3,5,18)-i.e., it occurred after our last common ancestor with chimpanzees but before the diaspora of present-day humans. This mutation was apparently caused by a human-specific sahAluY element that replaced an ancestral AluSq element found adjacent to exon 6 of the CMAH gene in the genomes of great apes (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation